MODERN PEDAGOGICAL FOUNDATIONS OF THE TRAINING PROCESS FOR FUTURE NURSES IN MEDICAL COLLEGES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article examines contemporary pedagogical foundations for the training of future nurses in medical colleges under conditions of modernization of the secondary vocational medical education system. Particular attention is paid to the competency-based approach as the methodological foundation of modern nursing education. Traditional and innovative teaching methods are analyzed, and the role of practice-oriented and simulation-based technologies in the development of students’ professional competencies is revealed. The research findings may be used to improve the educational process in medical colleges and enhance the quality of nurse training. The analysis demonstrates that the most effective directions for the modernization of nursing education include the implementation of the competency-based approach, the development of simulation-based and practice-oriented learning, the use of innovative and digital educational technologies, and the application of the credit-modular system. The main problems and contradictions in the implementation of modern pedagogical models are identified, and scientifically grounded recommendations for improving the professional training of future nurses are formulated.
Keywords: competency-based approach, nurse, secondary vocational education, medical college, innovative teaching methods, practice-oriented learning.